A case of tripterygium glycosides‐associated AGEP‐like drug reaction combined with bullous pemphigoid. Issue 4 (10th June 2021) - Sun, Ziwen; Zheng, Jianfeng; Yu, Ning; Chen, Jia; Ding, Yangfeng; Liu, Na
Abstract: Acute generalized exanthematous pustulosis (AGEP) is a severe cutaneous drug reaction. Bullous pemphigoid (BP) is an acquired autoimmune disease that might be associated with drugs. There is currently no report of tripterygium glycosides (TG)‐induced AGEP‐like lesions combined with BP. A 66‐year‐old male with a 20‐year history of psoriasis was prescribed oral TG at 1 mg/kg, three times a day, due to aggravated psoriasis. Seven days later, erythemas, and blisters appeared. After another 3 days, there were two types of blisters: (1) numerous small tension blisters with a lot of neutrophils on the top similar to AGEP combined with BP; (2) a BP. After intravenous injection of methylprednisolone and gamma globulin, the lesions were controlled. This patient developed two types of lesions, including one similar to AGEP combined BP (AGEP‐like) and a BP. It is a rare drug reaction induced by TG.